Effects of Previously Well-Developed Collateral Vessels on Left Internal Mammary Artery Graft Flow after Bypass Surgery - Ozdemir, Ozcan (2005)
Transthoracic Doppler ultrasonography can assess left internal mammary artery patency and flow after coronary artery bypass grafting. We aimed to show, by transthoracic Doppler ultrasonography, the early effects upon left internal mammary artery graft flow of preoperative collateral vessels supplying the left anterior descending artery. Thirty-four consecutive patients undergoing coronary artery bypass were prospectively enrolled: 19 patients with collateral vessels supplying the left anterior descending were compared with 15 patients without collaterals. After bypass, end-diastolic velocity, mean velocity, flow volume, and ejection fraction were significantly greater, and the resistivity index was lower in patients with collateral vessels. The changes in velocities, volume, resistivity index, and pulsatility index were also found to be greater in patients with collateral vessels than in those without collaterals. Collateral vessels were the only factor affecting the changes in end-diastolic volume, mean velocity, flow volume, and resistivity index in multivariate analysis. Three factors affected postoperative left ventricular ejection fraction: collateral vessels, preoperative ejection fraction, and changes in left internal mammary flow volume. We conclude that patients with well-developed collaterals to the left anterior descending have better flow in the left internal mammary graft and more significant improvement in left ventricular function after coronary bypass. The flow volume of the mammary graft and the improvement of ventricular systolic functions after coronary bypass might be presumed with the presence of grade 2 or 3 preoperative collateral vessels.